1976
DOI: 10.1095/biolreprod15.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Free and Conjugated Steroids in Maternal and Fetal Plasma in the Cow Near Term

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…Although E 1 S is not biologically active at the nuclear estrogen-receptor compared with weakly to moderately effective E1 and highly active E 2 β [15], measurement of E 1 S in maternal plasma and assessment of its function would provide an indirect estimation of E1. During the last week of gestation, both E 1 S and E 2 β increase markedly in peripheral blood and reach peak values around parturition [12,17,18]. These prepartum rises in maternal blood result from increased activity of 17α-hydroxylase, C-17, 20-lyase and aromatase [19,20].…”
mentioning
confidence: 99%
“…Although E 1 S is not biologically active at the nuclear estrogen-receptor compared with weakly to moderately effective E1 and highly active E 2 β [15], measurement of E 1 S in maternal plasma and assessment of its function would provide an indirect estimation of E1. During the last week of gestation, both E 1 S and E 2 β increase markedly in peripheral blood and reach peak values around parturition [12,17,18]. These prepartum rises in maternal blood result from increased activity of 17α-hydroxylase, C-17, 20-lyase and aromatase [19,20].…”
mentioning
confidence: 99%
“…These results show that early in pregnancy in cows that are to abort the progesterone secretion cannot be maintained and that estradiol, although it is less abundant than estrone, is a better indicator of the physiological state of pregnancy. Glencross et al (1973), Robertson (1974), Comline et al (1974) and Hoffman et al (1976) Lamond and Gaddy (1912) …”
mentioning
confidence: 99%
“…On the other hand, the concentrations of oestrogens are relatively high and vary among individuals (Challis et al, 1974;Hoffmann et al, 1976;Reimers et al, 1985). Conjugated oestrogens also exceed that of free oestrogens; however, oestradiol-17a-sulphate, but not oestronesulphate, is the major oestrogen in foetal blood (Hoffmann et al, 1976). It was suggested that oestrone (free and conjugated), which is produced and released from the cotyledons, must be reduced into oestradiol-17a when entering the foetal compartment (Hoffmann et al, 1979).…”
Section: Concentrations Of Progesterone and Oestrogens In Foetal Bloodmentioning
confidence: 99%
“…The placenta is the main source of oestrogens in the bovine pregnancy (Edqvist et al, 1973;Peterson et al, 1975;Hoffmann et al, 1976). Both oestrone and oestradiol were detected in cotyledonary and caruncular tissues from about the fourth month of gestation (Tsumagari et al, 1993).…”
Section: Oestrogen Productionmentioning
confidence: 99%